Trophic selectivity in aquatic isopods increases with the availability of resources. (25th February 2020) - Francois, Clémentine M.; Simon, Laurent; Malard, Florian; Lefébure, Tristan; Douady, Christophe J.; Mermillod‐Blondin, Florian
Abstract: Trophic selectivity has major influences on consumers' fitness, stability of predator and prey populations, and nutrient fluxes in food webs. Trophic selectivity occurs when the relative abundances of resources in a consumer's diet differ from their relative abundances in the environment. This discrepancy between resources abundance and use has been predicted to increase with the availability of resources in the environment. Trophic selectivity has also been predicted to increase with the heterogeneity of resources quality in the environment. Despite their ecological and evolutionary implications, conclusive in situ tests of these predictions are still lacking. We challenged these two predictions by studying 15 closely related species of isopods distributed along a wide range of resource availability (RA) (from 1.3 to 57.6 g of organic carbon per m 2 ). The dataset ranged from deep cave systems, considered as some of the most resource‐limited environments on Earth, to highly productive surface streams. For each species, we quantified the relative abundance of all available resources in the environment and estimated the heterogeneity in the stoichiometric quality of these resources. Isopod diet was determined using C and N stable isotopes and a Bayesian mixing model. The degree of trophic selectivity was then calculated for each species. By coupling a standardized quantification of trophic resources with a fine determination of diets using stable isotopes, we uncovered a positive relationship between RA and trophic selectivity. In contrast to our second prediction, trophic selectivity did not correlate with the heterogeneity of resources quality. Our results have important implications in trophic ecology by highlighting that RA was a main driver of trophic choices in aquatic invertebrates across a broad range of environments. These findings call for further evaluation of the mechanisms (e.g. trophic competition) causing the positive relationship between trophic selectivity and RA, as these mechanisms could be closely linked to those generating the documented relationship between species richness and productive energy. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.